Take my eyes [videorecording (DVD)] - Bollaín, Icíar, 1967-; Marull, Laia, 1973-; Tosar, Luis; Peña, Candela (New Yorker Video, 2006)
A terrified Pilar hastily flees from her husband Antonio's rage in the middle of the night with her young son as if her life depends on it. Reaching her sister Ana's house, Pilar breaks down in turmoil. Banging on Ana's front door is Pilar's husband, Antonio, who in a fit of rage screams for Pilar to return home. With ana's support, Pilar is determined to save herself from Antonio's rage. Yet the very passionate Antonio is far from a one-dimensional brute, and the bond between Pilar and Antonio is deep.